ANALISIS GEOSPASIAL PERMASALAHAN LAND SUBSIDENCE DAN PEMANFAATAN AIR DI WILAYAH PEKALONGAN - Junianto Sitompul, Roni
Pekalongan is one of the famous batik centers in Indonesia. In accordance with the economic development activities in the Pekalongan region causes huge enhancement of the amount of sewage and groundwater exploitation. Sewage disposal into rivers and groundwater exploitation continuously and excessively can cause environmental problems like polluted rivers, water table decline, land subsidence, distressed aquifer damage, seawater intrusion, flooding, and coastal flooding. These disasters can be classified into land subsidence and water disasters. Land subsidence and water disasters mappings are important to describe the negative effects caused by sewage disposal and groundwater exploitation excessively in the Pekalongan region. The disaster of land subsidence and water mappings used the data of land subsidence, seawater intrusion, polluted rivers, flooding, and coastal flooding. Then, the data were interpolated, delineated, and weighted to determine the affected and non-affected areas. Furthermore, an overlay was carried out to produce land subsidence and water maps. The results of the mapping were made into a grid to calculate the wide of the affected area. Geospatial analysis of land subsidence and water disasters is the closer the coast, the more the number of disasters. Land use that became affected areas were settlements covering an area of 5,396.15 Ha (35.93%), agriculture covering an area of 4,877.54 Ha (32.48%), a pond area of 2,260 Ha (15.05%), agriculture an area of 4,877.54 Ha (32.48%), a pond covering an area of 2,260 Ha (15.05%), swamps covering 2,106.07 Ha (14.02%), rivers covering 283.61 Ha (1.89%), industries covering 34.20 Ha (0.23%), open space green area of 61.67 Ha (0.41%). The total area affected was 1 disaster covering an area of 3,750.33 Ha, 2 disasters covering 3,692.20 Ha, 3 disasters covering 2,778.57 Ha, 4 disasters covering 1,539.99 Ha, 5 disasters covering 2,717.66 Ha, and 6 disasters covering 540, 48 Ha.